ANALISIS PENGARUH KEMUDAHAN, KENYAMANAN DAN EFISIENSI TERHADAP FREKWENSI PEMBELIAN PRODUK MELALUI INTERNET - Agus Wismo Widodo (Fakultas Teknik Universitas Persada Indonesia YAI, 2020)
The aim is to determine consumer behavior in deciding to buy products through the internet. This study uses a survey method of respondents through the internet with involved 125 responden consisting 0f 3 catagories age 15-25 years, aged 26 -35 years and those aged over 35 years. The results show that the ability of consumers to buy products through the internet depends on the amount of income. Income is grouped into three catagories, namely income of 1.000.000 - 5.000.000, 5.000.000 -15.000.000 and consumers who earn more than 15.000.000. the results of the analysis based on consumer characteristics show that 42.4% of consumers with an income of 5.000.000 – 15.000.000, while incomes of 1.000.000-5.000.000 anf above 15.000.000 are respectively 34.4 % and 23.2 %. While based on gender there is a positive and significant relationship with the frequency of purchases through the Internet. Gender factors influence the frequency of product purchases through the internet. For the age factor there is a positive and significant relationship to the frequency of product purchases. Young people between the ages of 26-35 years dominate the purchase of products through the internet, because they have mastered the technology and financially. They are also quite good. Keywords : Ease, Comport, efficiency, and frequency of product purchases.